2019
DOI: 10.1002/wps.20673
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of app‐supported smartphone interventions for mental health problems: a meta‐analysis of randomized controlled trials

Abstract: Although impressive progress has been made toward developing empirically-supported psychological treatments, the reality remains that a significant proportion of people with mental health problems do not receive these treatments. Finding ways to reduce this treatment gap is crucial. Since app-supported smartphone interventions are touted as a possible solution, access to up-to-date guidance around the evidence base and clinical utility of these interventions is needed. We conducted a meta-analysis of 66 random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
460
5
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 569 publications
(506 citation statements)
references
References 77 publications
31
460
5
10
Order By: Relevance
“…6 Likewise, we know that smartphone apps can be useful tools for some patients, but their efficacy more than doubles when used with a clinician. 7 In terms of disaster responses, the actual evidence that can be incorporated into clinical guidance today is minimal, 1 highlighting the need for urgent research. Codifying current evidence in preliminary guidelines and expanding research on real-world implementation and effectiveness will ensure the digital health tools are optimally used.…”
mentioning
confidence: 99%
“…6 Likewise, we know that smartphone apps can be useful tools for some patients, but their efficacy more than doubles when used with a clinician. 7 In terms of disaster responses, the actual evidence that can be incorporated into clinical guidance today is minimal, 1 highlighting the need for urgent research. Codifying current evidence in preliminary guidelines and expanding research on real-world implementation and effectiveness will ensure the digital health tools are optimally used.…”
mentioning
confidence: 99%
“…Thus, the generalizability of these findings is questionable. A meta-analysis by Linardon et al (4) included more data and a statistical analysis of effect sizes. Based on 66 RCTs of mental health EMI applications in clinical and nonclinical samples, they reported a reduction of stress and depressive and anxiety symptoms with small to medium effects (Hedge's g between 0.28 and 0.58).…”
Section: Evidence From Randomized Controlled Trialsmentioning
confidence: 99%
“…The umbrella term Ecological Momentary Intervention (EMI) labels a group of methods that provide clinical treatment via mobile devices in individuals' daily lives. The development and application of EMI are continuously increasing (1)(2)(3), related to the emergence of smartphone apps and the widespread availability of the internet (4,5). Today, EMI applications are offered as treatment of various different psychological and psychiatric disorders including anxiety disorders, depression, obsessive-compulsive disorders, and posttraumatic stress disorders (2,4,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings showed that, compared to waitlist control conditions, smartphone interventions significantly reduced symptoms of anxiety, with a medium effect size. A more recent meta-analysis identified 29 RCTs examining the effects of smartphone interventions on generalised anxiety symptoms and found these to be superior to any control condition, with a small effect size [29].…”
Section: Introductionmentioning
confidence: 99%